Conditions of Entrepreneurship Development Amongst Women in The Sector of Small and Medium-Sized Enterprises in Poland - Tomasz KOSMAN (Communications of International Proceedings, 2022)
Nowadays women in Poland as well as in the other European Union countries constitute a certain margin of untapped labour resources though they are frequently better educated. However, the unemployment rate is still higher among women than men.  Therefore, it is essential to boost entrepreneurship amongst women by means of law regulations, implementing best practices, as well as making use of appropriate tools. It is vital to use various forms of support, since there exist conditions and barriers which make it difficult for women to act in the job market properly as well as to run and develop their own businesses. In the contemporary world the importance of entrepreneurship among women is considerably growing. Technological development and the amount of highly educated women foster their entrepreneurship development, nevertheless they have to overcome a great deal of barriers. Various organisations and foundations launch indispensable support programmes for women which facilitate and encourage women to set up and run their own businesses. Moreover, on account of these programmes women constitute a substantial part of the group of company owners.
Keywords: Entrepreneurship among women; conditions of entrepreneurship development amongst women; barriers of entrepreneurship development amongst women; the support for entrepreneurship development amongst women.